Impact of logo wear on provider perception of patient - Bill Gombeski (The Beryl Institute, 2016)
Patient's appearance affects provider perception of patients and subsequent provider behavior. Based on anecdotal information, it was hypothesized that wearing a health organization's brand would result in a more positive perception of a patient by providers and subsequently a better patient experience. A study of 121 individuals with patient contact was conducted. Using photos of patients with and without a health care brand on their shirts, study subjects rated the attractiveness and willingness to engage with photos of patients. Patients with a Mayo brand and UK HealthCare brand showed some significant positive attractiveness over the same patient without the brand. Wearing a health organization brand may increase a patient's attractiveness. However, no differences in provider behavior were noted. Unexpectedly providers as a group viewed some patients significantly less desirable than others and indicated it would affect the amount of time they would spend and information they would share with a patient. Health care organizations need to regularly reinforce to their providers and front line staff, the human tendency to provide lower quality service and of care to less attractive or desirable patients.